Tumor genetic analyses of patients with metastatic melanoma treated with the BRAF inhibitor Dabrafenib (GSK2118436) - Nathanson, Katherine L. (2013)
PURPOSE: Dabrafenib is a selective inhibitor of V600-mutant BRAF kinase, which recently demonstrated improved progression free survival (PFS) as compared with dacarbazine, in metastatic melanoma patients. The current study examined potential genetic markers associated with response and PFS in the phase I study of dabrafenib. EXPERIMENTAL DESIGN: Baseline (pre-treatment or archival) melanoma samples were evaluated in 41 patients using a custom genotyping melanoma-specific assay, sequencing of PTEN, and copy number analysis using multiplex ligation amplification and array based comparative genomic hybridization. Nine patients had on-treatment and/or progression samples available. RESULTS: All baseline patient samples had BRAF(V600E/K) confirmed. Baseline PTEN loss/mutation was not associated with best overall response (BOR) to dabrafenib, but it showed a trend for shorter median progression free survival (PFS) (18.3 [95% confidence interval (CI) 9.1–24.3] vs. 32.1 weeks [95% CI 24.1–33], p=0.059). Higher copy number of CCND1 (p=0.009) and lower copy number of CDKN2A (p=0.012) at baseline were significantly associated with decreased PFS. Although no melanomas had high level amplification of BRAF, the two patients with progressive disease as their best response had BRAF copy gain in their tumors. CONCLUSIONS: Copy number changes in CDKN2A, CCND1, and mutation/copy number changes in PTEN correlated with the duration of PFS in patients treated with dabrafenib. The results suggest that these markers should be considered in the design and interpretation of future trials with selective BRAF inhibitors in advanced melanoma patients.